THE IMPORTANCE OF LEARNING PROCESS IN PSYCHOMOTOR THROUGH CAPACITY COORDINATIVE (Fiep Bulletin - online, 2015)
The Psychomotor is the science of man based on his own body and movements that interact with internal and external world. This relationship maturation offers great freedom of expression for each acquire and enhance the cognitive, affective and social skills. This study aims to enhance and emphasize the work of coordinative capacities for understanding the importance of psychomotor skills in the learning process of children through the development of these coordinative abilities. These capabilities are necessarily and compulsorily essential for determining the processes of motor control and regulation of the central nervous system, which will be on the basis for learning, execution condition and the domino of technicalities. The children need experiences and experiences of your own body to form and establish concepts of spatial orientation. It is up to the professional education make sense of this body that needs thought and movement to learn to relate and survive in this space. Knowing this body is to develop autonomy and make it able to survive culturally permeating an individual body to a body in full compliance with the company. Coordinative capabilities that are second WEINECK, 1999, balance, reaction, differentiation, change, rhythm, spatial orientation and motion concatenation surely lead these children to work the act of jogging, working to develop the intellect and the affections and will the child to meet and get to know the other emphasizing the individual into adulthood. The coordinative development of these capacities is the process of motor learning, as technical training is the ideal combination of coordinative abilities and limitations as strength, agility, flexibility, among several others who value and perfect promoting improvements in the individual as a whole.
Keywords: Psychomotor; Learning; Skills coordinative.